FIELD EXPERIENCE REPORT: CHANGING BEHAVIOR – SUGARY DRINKS - Htoo, Zaw Wai (My University, 2015)
My public health field experience was completed at the Riley County Research and Extension office at 110 Courthouse Plaza in Manhattan, KS, during January to March 2015, total 180 hour. The objective of K-State Research Extension is to help the community by providing evidence-based university knowledge in the most practical ways so that people can apply in real-life and benefit in many areas such as agriculture, economics, family life, youth development, community leadership and business. Cooperative Extension was established in 1914. Various level of government and land-grant universities funded the county extension programs to extend technical expertise and research findings to help people improving their homes, families, farms, business and communities54. In Riley County, Kansas State University is the land-grant university that supports the research extension54. The program is funded and guided by a partnership of federal, state and county government. The Riley County office is directed by a county Extension director, and there are four Extension agents, one receptionist and two assistants. The agents specialize in the disciplines of family and consumer sciences, 4-H, horticulture and agriculture54. I completed the internship under the supervision and guidance of Ms. Virginia (Ginny) Barnard, MPH, Family and Consumer Sciences Agent of the Riley County. Her specialization is in the areas of nutrition, food safety, health and indoor environments. Ginny has several program schedules and during my time the Head Start - Mothers (Parents) and Children Health and Nutrition Program was a new program possible to add into existing programs. That parents and children health and nutrition program (Head Start) interested me and Ginny also found that program fitted my education, previous experiences and passions. Therefore, after consultations of myself, Ginny and Program Director of Head Start, I agreed to focus on this program as my internship program assignment. Head Start/Early Head Start55 is a free, federally funded early childhood program. The program serves families with low incomes in Riley County and the Manhattan-Ogden School District with education, health, nutrition, and social services. Head Start enrolls children ages 3-5 years and offers full-day and half-day preschool classes. Early Head Start is a home visitation program that enrolls pregnant mothers and children from birth to 3 years of age. Head Start promotes the belief that parents are their child's lifelong teacher, so it supports the involvement of parents, efforts to reach goals, changes and transitions in the family's life. Head Start provides a supportive learning environment for children, parents, staff, and the community. During my field experience, I was able to provide nutrition education for parents and children relating to some nutrition concerns that were widespread in the community but not frequently addressed.
Keywords: Sugary drinks; Oral health; Public health; Public Health (0573)